EVALUASI DOKUMEN KURIKULUM PROGRAM STUDI PENDIDIKAN BAHASA JERMAN UNIVERSITAS NEGERI MALANG MENGACU PADA KKNI, SN-DIKTI, DAN AUN-QA - Rachma Shela Prabhandari; Primardiana Hermilia Wijayati (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2018)
This article is an evaluation study that aims to evaluate curriculum documents by describing learning outcome’s (LO) suitability contained in the curriculum 2016 of German Department with LO contained in Indonesia National Qualification Framework (INQF), National Standard of Higher Education (NSHE) and ASEAN University Network Quality Assurance (AUN-QA). The results showed that formulation of learning outcomes in the curriculum document of German Department especially on the components of attitudes and values, mastery of knowledge, general and special skills has been adjusted to the general description and description of the level of qualification 6 in Indonesia National Qualification Frameworkand general attitude and skill formulation in NSHE. Based on the review in terms of the document, the curriculum of German Department has been accordance with INQF and NSHE, but it is still not suitable especially in the criteria Programme Structure and Content.